Leadership and the New Science: Learning About Organization from an Orderly UniversityLeadership and the New Science: Learning About Organization from an Orderly University, by WheatleyMargaret J.. San Francisco: Berrett-Koehler, 1992, 164 pp., cloth, ISBN: 1-881052-01-X. - Lundberg, Craig C. (Academy of Management Review, 1994)
The article reviews the book ?Leadership and the New Science: Learning About Organization from an Orderly University,? by Margaret J. Wheatley.